Densitometric test in differential diagnosis of short stature children - Łysoń-Wojciechowska, Grażyna; Romer, Tomasz; Skawiński, Waldemar (Anthropological Review, 1999)
The aim of the study is to compare the dimensions and optical density of the second metacarpal bone in children with short stature caused by idiopathic growth hormone deficiency (IGHD), and children with short stature, but normal level of growth hormone. The diagnostic importance of the obtained results is assessed.